Pro-toxic dehydropyrrolizidine alkaloids in the traditional Andean herbal medicine “asmachilca” - Colegate, Steven M. (J Ethnopharmacol, 2015)
ETHNOPHARMACOLOGICAL RELEVANCE: Asmachilca is a Peruvian medicinal herb preparation ostensibly derived from Eupatorium gayanum Wedd. = Aristeguietia gayana (Wedd.) R.M. King & H. Rob. (Asteraceae: Eupatorieae). Decoctions of the plant have a reported bronchodilation effect that is purported to be useful in the treatment of respiratory allergies, common cold and bronchial asthma. However, its attractiveness to pyrrolizidine alkaloid-pharmacophagous insects indicated a potential for toxicity for human consumers. AIM OF THE STUDY: To determine if commercial asmachilca samples, including fully processed herbal teas, contain potentially toxic 1,2-dehydropyrrolizidine alkaloids. MATERIALS AND METHODS: Two brands of “Asmachilca” herbal tea bags and four other commercial samples of botanical materials for preparing asmachilca medicine were extracted and analyzed using HPLC-esi(+)MS and MS/MS for the characteristic retention times and mass spectra of known dehydropyrrolizidine alkaloids. Other suspected dehydropyrrolizidine alkaloids were tentatively identified based on MS/MS profiles and high resolution molecular weight determinations. Further structure elucidation of isolated alkaloids was based on 1D and 2D NMR spectroscopy. RESULTS: Asmachilca attracted many species of moths which are known to pharmacophagously gather dehydropyrrolizidine alkaloids. Analysis of 5 of the asmachilca samples revealed the major presence of the dehydropyrrolizidine alkaloid monoesters rinderine and supinine, and their N-oxides. The 6(th) sample was very similar but did not contain supinine or its N-oxide. Small quantities of other dehydropyrrolizidine alkaloid monoesters, including echinatine and intermedine, were also detected. In addition, two major metabolites, previously undescribed, were isolated and identified as dehydropyrrolizidine alkaloid monoesters with two “head-to-tail” linked viridifloric and/or trachelanthic acids. Estimates of total pyrrolizidine alkaloid and N-oxide content in the botanical components of asmachilca varied from 0.4 – 0.9% (w/dw, dry weight) based on equivalents of lycopsamine. The mean pyrrolizidine alkaloid content of a hot water infusion of a commercial asmachilca herbal tea bag was 2.2 ± 0.5 mg lycopsamine equivalents. Morphological and chemical evidence showed that asmachilca is prepared from different plant species. CONCLUSIONS: All asmachilca samples and the herbal tea infusions contained toxicologically-relevant concentrations of pro-toxic 1,2-dehydropyrrolizidine alkaloid esters and, therefore, present a risk to the health of humans. This raises questions concerning the ongoing unrestricted availability of such products on the Peruvian and international market. In addition to medical surveys of consumers of asmachilca, in the context of chronic disease potentially associated with ingestion of the dehydropyrrolizidine alkaloids, the botanical origins of asmachilca preparations require detailed elucidation.